Determinants of Career Choices Among Accounting Students: A Motivational Theory Perspective - Syaipudin, Usep; Fathia, Syaharani Noer; Majidah, Rona; Wulan, Diajeng Fitri (E-Jurnal Akuntansi; Vol 35 No 4 (2025)DO - 10.24843/EJA.2025.v35.i04.p09, 2025)
This study aims to identify the factors influencing accounting students' career choices within the framework of Herzberg's two-factor motivation theory. The research employs a quantitative approach using a survey method involving accounting students from various public universities in Southern Sumatra. The findings reveal that intrinsic factors such as work motivation, job satisfaction, personal ability, personal interest, as well as personal values and ethics significantly influence students' interest in pursuing a career as a public accountant. Conversely, extrinsic factors such as job availability, job risk, and financial rewards do not show a significant influence. This study recommends that universities place more emphasis on developing students' intrinsic motivation in preparing them to become professionals in the accounting field. Keywords: Accounting Career; Motivation Theory;  Accounting Students; Public Accountant